Front Cover: Electrochemical Pretreatment of Solid‐Electrolyte Interphase Formation for Enhanced Li4Ti5O12 Anode Performance in a Molten Li−Ca Binary Salt Hydrate Electrolyte (ChemElectroChem 11/2022). Issue 11 (3rd May 2022) - Kondou, Shinji; Watanabe, Yoshifumi; Dokko, Kaoru; Watanabe, Masayoshi; Ueno, Kazuhide
Abstract : The Front Cover illustrates that less‐water‐soluble Ca‐based solid electrolyte interphase formed in a Li–Ca binary salt hydrate electrolyte effectively mitigates electrochemical reduction of water, leading to improvement in the cycle performance of a Li4 Ti5 O12 electrode. More information can be found in the Research Article by S. Kondou et al .